Pengaruh Media Sosial Instagram, Variasi Produk dan Kualitas Produk Terhadap Minat Beli - Ali Maksum; Dian Prasetyo Widyaningtyas; Bonaventura Hendrawan Maranata (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The interest in purchasing is an essential aspect to consider in managing an institution or company to achieve its goals. This research aims to determine the influence of Instagram social media on purchasing interest at Maju Aquarium Fish Store, the influence of product variation on purchasing interest at Maju Aquarium Fish Store, the influence of product quality on purchasing interest at Maju Aquarium Fish Store, and the simultaneous influence of Instagram social media, product variation, and product quality on Maju Aquarium Fish Store. This research uses descriptive analysis. The method applied is Multiple Linear Regression Analysis. The data analysis technique applies the SPSS program to process and analyze data. Quantitative descriptive is applied as a method in this study in which variables are measured through a Likert scale. Data collection methods are carried out by distributing questionnaires to respondents. The research sample is consumers of Maju Aquarium Fish Store. The results of this research state that: (1) Instagram social media has a positive and significant influence on purchasing interest at Maju Aquarium Fish Store with a significance of 0.015 < 0.05. (2) Product variation has a positive and significant influence on purchasing interest at Maju Aquarium Fish Store with a significance of 0.001 < 0.05. (3) Product quality has a positive and significant influence on purchasing interest at Maju Aquarium Fish Store with a significance of 0.001 < 0.05. Instagram social media, product variation, and product quality simultaneously provide a significant influence of 0.001 > 0.05.